Termobiologia da germinação de sementes de Sesbania virgata (Fabaceae) - Zayat, André Georges (1996)
Some Sesbania species, particularly S. virgata (Caz.) Pers. are useful in revegetation programs of flooded areas, due to its high tolerance to anoxia and soil mineral deficiences. Most information of Sesbania seeds are on their chemical properties or the effects of physical and chemical treatments on their seed coat. Although the propagation of this specie using seeds is common, there is no physiological information reguarding the germination process. The treatments were induced in 80 different isothermical temperatures in a thermogradient block for germination experiments. Parameters such as seed water content and photoblastism, its germinability, germination time and rate, viability, activation enthalpy and protein profile were analised The seeds are caracterized as orthodoxes and light insensitive. They present high germinability from 8,9 to 36,6°C, optimum germination rate from 31,0 to 34,6°C, and their low and high temperature limits for germination are 7,0 to 7,4°C and 39,8 to 40,3°C, respectively. Although the seeds can stay viable for more than 578 hours at low temperature, their germination assincrony increases as the temperature decrease. On the other hand, seeds mantained at high temperatures for periods no more than 72 hours, germinate quickly and with high sincronization. It can be seen that in temperatures lower than 11,0°C and higher than 35,1°C, the germination process limitation, suggested by the ativation enthalpy energy parameter, is due to thennodesnaturation or transconformation of proteins. On the other side, at some low and some high temperatures we can see that there is no synthesis or degradation of some proteins, that are present in the protein control profile. Also, at high temperatures, two proteins of low molecular weight are synthesised, and are probably related to their termotolerance.